2013
DOI: 10.1111/joms.12025
|View full text |Cite
|
Sign up to set email alerts
|

Managing Partners and Management Professionals: Institutional Work Dyads in Professional Partnerships

Abstract: This study presents an empirical analysis of the micro‐dynamics of institutional work. Examining the ‘corporatization’ of large international law firm partnerships, the study identifies the dyadic relationship that develops between two different types of professionals, the managing partner and management professional, and demonstrates how their relationship becomes a key mechanism for institutional work. The study shows how, by working together, these individuals take advantage of differences in their relative… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
147
0
7

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(155 citation statements)
references
References 58 publications
1
147
0
7
Order By: Relevance
“…In line with prior studies of institutional work (e.g., Empson et al, 2013;Slager et al, 2012), this process was of a more deductive nature as it relied on pre-existing repertoires of institutional work (e.g., Lawrence and Suddaby, 2006). We found that some of the purposive activities aimed at turning CSR into strategy clustered into practices that correspond to existing types of institutional work.…”
Section: Discussionmentioning
confidence: 58%
“…In line with prior studies of institutional work (e.g., Empson et al, 2013;Slager et al, 2012), this process was of a more deductive nature as it relied on pre-existing repertoires of institutional work (e.g., Lawrence and Suddaby, 2006). We found that some of the purposive activities aimed at turning CSR into strategy clustered into practices that correspond to existing types of institutional work.…”
Section: Discussionmentioning
confidence: 58%
“…The solution to this paradox of embedded agency lies in the duality of social action (Giddens, 1984), meaning that institutions structure the expectations and actions of people and that agency simultaneously either reproduces or transforms these underlying structures of meaning. In this respect the relatively recent approaches of institutional entrepreneurship (Maguire, Hardy, & Lawrence, 2004;Munir & Phillips, 2005) and of institutional work (Empson, Cleaver, & Allen, 2013;Lawrence, Leca, & Zilber, 2013;Smets, Morris, & Greenwood, 2012) call for a comprehensive consideration of the conscious and unconscious practices of individual and collective actors in the transformation of institutions. One important step forward in this endeavor comes from a neostructural approach to institutionalization that emphasizes the impact that relational infrastructure in social networks, such as social status and niche, have on norm alignment and institutional transformation (Lazega, 2001;Lazega, Quintane, & Casenaz, 2017).…”
Section: Institutions Change and Social Outcomes: Key Challengesmentioning
confidence: 99%
“…Cooper, Hinings, Greenwood, & Brown, 1996;Empson, Cleaver, & Allen, 2013;Lawrence, Malhotra, & Morris, 2012). Considerando sua importância na sociedade e as transformações pelas quais estão passando, as organizações de serviços profissionais têm atraído cada vez mais a atenção dos teóricos organizacionais (Greenwood, Li, Prakash, & Deephouse, 2005).…”
Section: Introductionunclassified